Do Fork-tailed Flycatchers (Tyrannus s. savana) stop to molt during fall migration? - Jahn, Alex E. [UNESP]; Guaraldo, André C. (Springer Nature, 2018)
Fork-tailed Flycatchers (Tyrannus s. savana) breed from central to southern South America, then migrate to northern South America, where they undergo a winter molt. However, exactly when this winter molt begins is not known. Previous research showed that some Fork-tailed Flycatchers stopover for an extended period in Mato Grosso do Sul in late January/early February, during fall migration. We hypothesized that these flycatchers are suspending fall migration to initiate flight feather molt, as do congeners in North America. In February 2016, we located a roost of >100 migratory flycatchers in Mato Grosso do Sul state and captured two adults and two juveniles, one of which was an adult female that was symmetrically molting the first primary feather. This is the furthest south that this species has been found molting flight feathers and suggests that some Fork-tailed Flycatchers undertake fall molt-migration to Mato Grosso do Sul. Further research on the relationship between timing of molt and migration of this and other birds that migrate within South America will be essential to evaluate the evolution of their life history strategies, seasonal interactions, and limitations they face throughout the year.
Keywords: Intra-tropical migration; Mato grosso do sul; Post-reproductive; Remiges